The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1038/s41413-021-00171-z
|View full text |Cite
|
Sign up to set email alerts
|

The ERα/KDM6B regulatory axis modulates osteogenic differentiation in human mesenchymal stem cells

Abstract: Osteoporosis is a highly prevalent public health burden associated with an increased risk of bone fracture, particularly in aging women. Estrogen, an important medicinal component for the preventative and therapeutic treatment of postmenopausal osteoporosis, induces osteogenesis by activating the estrogen receptor signaling pathway and upregulating the expression of osteogenic genes, such as bone morphogenetic proteins (BMPs). The epigenetic regulation of estrogen-mediated osteogenesis, however, is still uncle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…KDM6B demethylates H3K27me3 to promote the expression of Bmp2 , Bmp4 , Runx2 and Hoxc6-1 and induce osteogenic commitment of BM-MSCs, thus elevating bone mass in OVX and aged mice [ 54 , 55 ]. Similar results have also been demonstrated in human dental MSCs [ 56 ]. KDM7A (also called KIAA1718 or JHDM1D) has demethylase activity for H3K27me1/me2 and H3K9me1/me2 [ 57 ], and can enhance adipogenesis and weaken osteogenesis by demethylating H3K9me2 and H3K27me2 on the promoters of Sfrp1 and C/ebpα in mouse primary BM-MSCs and ST2 cells [ 58 ].…”
Section: Regulation and Functions Of Histone Modifications In Bm-mscssupporting
confidence: 89%
“…KDM6B demethylates H3K27me3 to promote the expression of Bmp2 , Bmp4 , Runx2 and Hoxc6-1 and induce osteogenic commitment of BM-MSCs, thus elevating bone mass in OVX and aged mice [ 54 , 55 ]. Similar results have also been demonstrated in human dental MSCs [ 56 ]. KDM7A (also called KIAA1718 or JHDM1D) has demethylase activity for H3K27me1/me2 and H3K9me1/me2 [ 57 ], and can enhance adipogenesis and weaken osteogenesis by demethylating H3K9me2 and H3K27me2 on the promoters of Sfrp1 and C/ebpα in mouse primary BM-MSCs and ST2 cells [ 58 ].…”
Section: Regulation and Functions Of Histone Modifications In Bm-mscssupporting
confidence: 89%
“…It has been reported that lysine-specific demethylase 4B (KDM4B) and lysine-specific demethylase 6B (KDM6B) are most strongly induced by bone morphogenetic protein (BMP)-4/7 and promote osteogenic differentiation of human MSCs . KDM6B is recruited to the BMP2 and HOXC6 promoters, resulting in the removal of H3K27me3 markers and activation of the transcription of BMP2 and HOXC6 . Jmjd3 (KDM6B)-mediated H3K27 demethylation is considered a crucial factor for regulating M2 macrophage development, leading to anti-helminth host responses .…”
Section: Introductionmentioning
confidence: 99%
“… 9 KDM6B is recruited to the BMP2 and HOXC6 promoters, resulting in the removal of H3K27me3 markers and activation of the transcription of BMP2 and HOXC6. 10 Jmjd3 (KDM6B)-mediated H3K27 demethylation is considered a crucial factor for regulating M2 macrophage development, leading to anti-helminth host responses. 11 In addition, macrophages are well known to play a pivotal role in the induction of bone mesenchymal stem cells toward osteoblastic fate.…”
Section: Introductionmentioning
confidence: 99%
“…This favors adipogenic and inhibits osteogenic differentiation potential of bone marrowmesenchymal stromal cells (BM-MSCs). Conversely, the H3K27me3 demethylases, lysine demethylase 6A (KDM6A) (also known as UTX) and lysine demethylase 6B (KDM6B) (JMJD3) inhibit adipogenesis and promote osteogenesis, suggesting a key role for H3K27-centered epigenetic switch in stromal cell fate specification (21)(22)(23)(24). KDM6B is widely known for its role during inflammatory response and harbors NF-κB binding sites in its promoter (25,26).…”
Section: Introductionmentioning
confidence: 99%